What has happened to college teacher pay in England? - Luke Sibieta; Imram Tahir (Institute for Fiscal Studies (IFS), 2023)
In the last few months, there has been a series of strikes by teachers in further education colleges across England over pay and conditions, and more strikes look set to impact the post-16 education sector this year. With inflation at around 10%, college teachers have experienced large real-terms salary cuts this year, and these follow a sustained period of real-terms cuts to pay. In this report, we set out how college teacher pay has changed over time, we compare the pay of college teachers with that of school teachers and we look at staff retention levels in schools and colleges. Note that the analysis on pay focuses on the roughly 50,000 teachers in general further education colleges across England, so does not include teachers in sixth-form colleges, whereas the analysis on retention levels covers both.
Keywords: 330; Education and skills; Government finances and spending; Education spending; Education; Further education; Labour supply and workforce; Skills; Schools